2019
DOI: 10.1101/840629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Ultrastructural Changes of PSD and Extrasynaptic Axon-spine Interface Membrane during LTP Induced in Single Dendritic Spine

Abstract: Structural plasticity of dendritic spines is considered to be the basis of synaptic plasticity, learning and memory. Here, we performed ultrastructural analysis of spines undergoing LTP using a novel high throughput correlative light-electron microscopy approach. We found that the PSD displays rapid (< 3 min) reorganization of its nanostructure, including perforation and segmentation. This increased structural complexity is maintained over intermediate and late phases of LTP (20 and 120 min). In a few spines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The actin polymer network is reorganized ( Obashi et al, 2019 ), and the SER visits within a spine transiently ( Perez-Alvarez et al, 2020 ). Also, PSD shape becomes more complex ( Sun et al, 2019 Preprint ). These physical changes should occur in concert and will affect molecular composition and biochemical signaling through diffusional regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actin polymer network is reorganized ( Obashi et al, 2019 ), and the SER visits within a spine transiently ( Perez-Alvarez et al, 2020 ). Also, PSD shape becomes more complex ( Sun et al, 2019 Preprint ). These physical changes should occur in concert and will affect molecular composition and biochemical signaling through diffusional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the shape of PSDs inside spines induced by sLTP was analyzed by CLEM ( Sun et al, 2019 Preprint ). It was shown that rearrangements of PSD shape occurred immediately after induction of sLTP (<3 min), and the PSD took more complex morphology.…”
Section: Molecular Crowding In the Psdmentioning
confidence: 99%
“…Excitatory synaptic strength is proportional to the spine head volume; therefore, the increase in head volume may be necessary to support the enduring enhancement of synaptic transmission during long–term potentiation (LTP). Concomitant with the spine head remodeling, the PSD also changed its shape from the macular type to the perforated and segmented types (Sun et al, 2019 ). Furthermore, the PSD area also increased in response to LTP stimulation (Sun et al, 2019 ) and this may be necessary to recruit more AMPA-type receptors to the synapses.…”
Section: Retrospective Em Studies Of Dendritic Spinesmentioning
confidence: 99%
“…Concomitant with the spine head remodeling, the PSD also changed its shape from the macular type to the perforated and segmented types (Sun et al, 2019 ). Furthermore, the PSD area also increased in response to LTP stimulation (Sun et al, 2019 ) and this may be necessary to recruit more AMPA-type receptors to the synapses. However, for at least 30 min after LTP stimulation, PSD size did not seem to increase proportionally with head volume (Bosch et al, 2014 ; Sun et al, 2019 ).…”
Section: Retrospective Em Studies Of Dendritic Spinesmentioning
confidence: 99%
See 1 more Smart Citation